Development Of Local Tourism Economy Based On Maqasid Sharia: Participatory Appraisal Of Competitive Advantage - Siti Fatimatul Khasanah (Jurnal Syntax Admiration, 2023)
This study aims to analyze the development of the local tourism economy with a participatory appraisal of competitive advantage (PACA) approach through the perspective of maqashid sharia. By taking a case study in Red Island, Sumberagung Village, Pesanggaran District, Banyuwangi Regency, this research uses a qualitative approach with descriptive analysis. Data collection is done by observation, interview, and documentation techniques. The subject of the study was determined by purposive techniques. This study found that there are two PACA indicators that meet four of the six elements of sharia maqashid in the local tourism economy on Red Island. This study recommends strengthening institutional synergies between the government, private sector, and the community to create more value in the management of the tourism sector so that all elements in Sapta Pesona can be fulfilled so as to have a positive impact on local communities in line with sharia maqashid.